Penguatan Kapasitas Kelembagaan dalam Perencanaan Pembangunan Desa - Danar, Oscar Radyan; Novita, Asti Amelia; Prakasa, Yudha; Rachman, Fatur (Jurnal Ilmiah Administrasi Publik, 2021)
This study aims to analyze the efforts of strengthening the institutional capacity of the village government in the village development planning process. It is conducted in Banjar Village and Tamansari Village, Licin District, Banyuwangi Regency, East Java. Village development planning is one of the primary steps to translate the vision, missions, goals and objectives of the village. However, the lack of institutional capacity and the capability of the village apparatus is often the reason why village development planning cannot run optimally. This study uses a descriptive method with a qualitative approach while the data collection method in this study uses a literature study that is equipped with observations and interviews. The results showed that Banjar Village and Tamansari Village had carried out procedural and substantive planning but development planning in the two villages was still not optimal. This is indicated by the minimal capacity of planning apparatus resources as well as weak institutional and organizational capacities so that training is needed to maximize the quality of village development planning.